Hungary : Report on the Observance of Standards and Codes-Data Module and Fiscal Transparency-Updates. (IMF Staff Country Reports; Country Report, 2002)
This report presents an updates on the Observance of Standards and Codes-Data Module and Fiscal Transparency for Hungary. Hungary continues to observe the Special Data Dissemination Standard specifications for the coverage, periodicity, and timeliness of all data categories, including the detailed template on international reserves and foreign currency liquidity, and for the dissemination of advance release calendars. Progress has been made in the project to revise the data on imputed rents, currently extrapolated from 1993 data, on the basis of more up-to-date survey data.